2011
DOI: 10.1038/bmt.2010.347
|View full text |Cite
|
Sign up to set email alerts
|

A parainfluenza-3 outbreak in a SCT unit: sepsis with multi-organ failure and multiple co-pathogens are associated with increased mortality

Abstract: The estimated frequency of parainfluenza virus 3 (PIV-3) infections following haematopoietic SCT (HSCT) is 2-7%, whereas reported mortality ranges from 18 to 33%. We report a retrospective outcome analysis following an outbreak of PIV-3 infection in our transplant unit. A total of 16 HSCT patients developed PIV-3 infection. All patients had upper respiratory tract infection, whereas lower respiratory tract infection occurred in 8 patients. Overall, 13 patients were treated with aerosolised Ribavirin (2 g t.d.s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 24 publications
(46 reference statements)
0
36
0
Order By: Relevance
“…[1][2][3][4]8,12,[14][15][16][17][18][19][20][21] Furthermore, the development of LRTI has been consistently associated with significantly higher risk of death. 12,13,17,18 Early intervention with antiviral therapy has been demonstrated to reduce the risk of progression to pneumonia 7 and may lead to improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4]8,12,[14][15][16][17][18][19][20][21] Furthermore, the development of LRTI has been consistently associated with significantly higher risk of death. 12,13,17,18 Early intervention with antiviral therapy has been demonstrated to reduce the risk of progression to pneumonia 7 and may lead to improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…Paramyxoviruses, particularly respiratory syncytial virus (RSV), human metapneumovirus, and the human parainfluenza viruses (HPIVs), cause the majority of childhood croup, bronchiolitis, and pneumonia (1). In adults, these viruses cause about two-thirds of respiratory illnesses, with high mortality in immunocompromised persons (2); for example, HPIV3 accounts for 90% of the respiratory illnesses in hematopoietic stem cell transplant patients (3) and carries high mortality (3)(4)(5)(6)(7)(8). There are no effective vaccines or treatments for the HPIVs.…”
mentioning
confidence: 99%
“…29 The consequent greater susceptibility to pulmonary copathogens has been shown to substantially increase mortality in PIV3-infected patients with LRTI. 5,8,30 The early initiation of broad-spectrum antibiotic prophylaxis for bacterial infection on admission for all individuals with LRTI may have contributed substantially the reduced mortality in the study group.…”
Section: Figurementioning
confidence: 98%
“…Possible reasons include low numbers of pulmonary co-pathogens (6/32; 19%) in PIV3-infected subjects, prompt initiation of broadspectrum antibiotics (31/32; 97%) and only a small number of severely immunosuppressed HSCT recipients in our cohort (8/32; 25%), a group which in previous studies have shown the highest mortality (up to 60%) in those with LRTIs. 4,5,8,9,27,28 PIV3, in common with other respiratory viruses, may predispose to secondary bacterial infections by epithelial damage, impairment of ciliary function and triggering of host-inflammatory responses. In addition, bacterial infection may be promoted by increased expression of bacterial receptors on PIV3-infected cells.…”
Section: Figurementioning
confidence: 99%